What is the evidence of a role for host genetics in susceptibility to influenza A/H5N1? - Horby, P; Sudoyo, H; Viprakasit, V; Fox, A; Thai, P; Yu, H; Davila, S; Hibberd, M; Dunstan, S; Monteerarat, Y; Farrar, J; Marzuki, S; et al. (2010)
The apparent family clustering of avian influenza A/H5N1 has led several groups to postulate the existence of a host genetic influence on susceptibility to A/H5N1, yet the role of host factors on the risk of A/H5N1 disease has received remarkably little attention compared to the efforts focused on viral factors. We examined the epidemiological patterns of human A/H5N1 cases, their possible explanations, and the plausibility of a host genetic effect on susceptibility to A/H5N1 infection. The preponderance of familial clustering of cases and the relative lack of non-familial clusters, the occurrence of related cases separated by time and place, and the paucity of cases in some highly exposed groups such as poultry cullers, are consistent with a host genetic effect. Animal models support the biological plausibility of genetic susceptibility to A/H5N1. Although the evidence is circumstantial, host genetic factors are a parsimonious explanation for the unusual epidemiology of human A/H5N1 cases and warrant further investigation. Copyright © 2010 Cambridge University Press.